SIMPLE PRESENT IN AL QURAN SURAH AL BAQARAH JUZ 1 - YUSNI SINAGA (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Language is the main tool needed in an interaction or communication. Every meeting of two elements definitely requires a medium to meet as well as humans. In a meeting of two or more people, a tool is needed so that the two humans can communicate. Language is the main tool used by two people in carrying out a communication. Because Allah SWT created humans with different tribes and nations and have different languages ​​with the aim of getting to know each other. The wider the communication carried out, the more languages ​​that must be mastered. Thus increasing mastery of a language is needed along with increasing communication carried out. The level of language in question is; mother tongue, regional language, national language and international language. The Qur'an as a way of life and the legal basis for all human activities has explained the importance of mastering language for humans, such as mastering English. Key words; Simple Present Tense, Al quran, Al Baqarah Ab